Synthesis of Indolo[1,2-a]quinoxalinones through Palladium/Copper-Cocatalyzed Oxidative Isocyanide-Insertion Cyclization of Indoles and Hydrolysis of Enamines - Sha, Xuan; Ren, Jie; Hu, Yi-ran; Zhao, Yun-yi; Wu, Shi-ying; Yang, Rui; Chen, Yao; Ji, Fei (Synlett, 2021)
A novel Pd/Cu-cocatalyzed isocyanide-insertion cyclization of indoles and hydrolysis of enamines has been developed for the construction of indolo[1,2-a]quinoxalinones. A secondary amine group on the N-phenylindole skeleton acts as an important directing groups that participates in activation of the C(2)-position of the indole and the subsequent isocyanide-insertion cyclization. The fragile generated enamine bond is easily hydrolyzed by the acid medium to give the corresponding quinoxalinone skeleton. This regioselective and high-yielding transformation, which avoids the use of hazardous CO gas, might be extendable to syntheses of natural polycyclic products.
Keywords: isocyanide insertion; C–H bond activation; enamines; hydrolysis; indoloquinoxalinones